STRATEGIC PLANNING AND ORGANIZATION OF SYSTEM MONITORING OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF YOUTH POLICY - Obikhod M.M. (Pressing Problems of Public Administration, 2017)
The current state and principles of strategic planning, monitoring and evaluation in youth policyare analyzed. The process of formation of National indicators of youth policy, based on theoreticaland methodological principles of youth policy evaluation of the countries of the European Union,is considered. The proposals on organizing a modern system for monitoring and evaluating theimplementation of youth policy are formulated.